2011
DOI: 10.1097/shk.0b013e3181fd0700
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Requires Endothelial Nitric Oxide Synthase to Counteract TNF-α-Induced Microcirculatory Dysfunction in Murine Striated Muscle

Abstract: In the present study, we aimed to evaluate whether erythropoietin (EPO) treatment may exert nonhematopoietic endothelial protection against TNF-[alpha]-induced microvascular inflammation and to determine the involvement of the nitric oxide (NO)-producing enzyme isoforms endothelial NO synthase (eNOS) and inducible NO synthase (iNOS). Murine dorsal skinfold chambers of wild-type (WT) animals were topically stimulated with TNF-[alpha] after pretreatment with epoetin beta (1,000 IU/kg body weight i.p.) or physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, the NO leads to up-regulation of EpoR in these cells suggesting a coordinated response of these signaling molecules ( 53 ). In studies of sepsis in which tumor necrosis factor induces microvascular inflammation in striated muscle, Epo ameliorates the microvascular damage by an eNOS dependent mechanism but the protective effect is independent of iNOS ( 54 ). Similarly, Epo prevents sepsis-related acute kidney in rats by up-regulating eNOS ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NO leads to up-regulation of EpoR in these cells suggesting a coordinated response of these signaling molecules ( 53 ). In studies of sepsis in which tumor necrosis factor induces microvascular inflammation in striated muscle, Epo ameliorates the microvascular damage by an eNOS dependent mechanism but the protective effect is independent of iNOS ( 54 ). Similarly, Epo prevents sepsis-related acute kidney in rats by up-regulating eNOS ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the tissue‐protective effect is mediated by NO originating from the endothelium. This effect has been demonstrated both in wild‐type as well as in iNOS knockout mice (iNOS −/− mice) but not in endothelial (e)NOS knockout mice (eNOS −/− mice) . The authors have also demonstrated in an immunohistochemical assay that activated macrophages were almost not present in the perivenular tissue of EPO‐pretreated wild‐type and iNOS −/− mice when compared to eNOS −/− mice .…”
Section: Epo‐induced Effects In Physiological Wound Healing Of the Skinmentioning
confidence: 79%
“…This effect has been demonstrated both in wild‐type as well as in iNOS knockout mice (iNOS −/− mice) but not in endothelial (e)NOS knockout mice (eNOS −/− mice) . The authors have also demonstrated in an immunohistochemical assay that activated macrophages were almost not present in the perivenular tissue of EPO‐pretreated wild‐type and iNOS −/− mice when compared to eNOS −/− mice . The current data obtained from in vivo experiments imply the following: The pleiotropic functions of EPO are most probably triggered by a variety of mechanisms that are either dependent or independent of NO.…”
Section: Epo‐induced Effects In Physiological Wound Healing Of the Skinmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the mechanism of EPO protection against TNF-α depends on NO derived from endothelial cells [53]. …”
Section: The Influence Of Epo On Inflammation and Fibrosismentioning
confidence: 99%